Abnormal Change in Spring Snowmelt Over Eurasia and Its Linkage to the East Asian Summer Monsoon: The Hydrological Effect of Snow Cover - Xu, Bei; Chen, Haishan; Gao, Chujie; Zeng, Gang; Huang, Qinghan (Frontiers in Earth Science, 2021)
In this study, the relationship between Eurasian spring snowmelt and the East Asian summer monsoon (EASM), and its related mechanisms are investigated using observational and reanalysis data. Our analyses reveal that the interannual change of spring snowmelt over Eurasia is strongly linked to the EASM circulation variation and its corresponding summer precipitation in China. It’s noteworthy that soil moisture anomaly caused by the snow hydrological effect (i.e., snowmelt) plays a bridging role in connecting the Eurasian snow cover and the EASM. The results show that increased spring snowmelt over Siberia induces anomalously higher soil moisture from spring to the following summer, thus continuously lowering the local temperature. Such a cooling effect leads to a weakened meridional temperature gradient and a decreased baroclinicity between north Eurasia and the Arctic Ocean. Consequently, the variation in atmospheric baroclinicity induced by the nonuniform heating of land surface exerts a significant impact on the synoptic eddy. The eddy forcing gives a positive feedback on intensification of the wave train over north Eurasia. Finally, the atmospheric circulation responses weaken the EASM and influence summer precipitation over China, producing excessive precipitation over most regions of South China and deficient rainfall over Northeast and North China. Our study emphasizes the hydrological effect of the sub-seasonal change of spring snow cover over Siberia, which has a significant linkage to the variation of the EASM intensity. The resultant changes in the EASM lead to an abnormal meridional dipole pattern of summer precipitation over China. These findings will contribute to the seasonal prediction of monsoon precipitation.